RECONSTRUCTING YOUTH SPIRITUALITY THROUGH TRANSCENDENTAL DA’WAH MANAGEMENT: TOWARD A HYBRID MODEL OF SUFI ORGANIZATIONAL PRACTICE - fahmi ulum; Arsam (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
This study aimed to analyze the formulation, implementation, and effectiveness of the sufistic da’wah management strategy applied by Jam’iyah Ahlith-Thariqah al-Mu’tabarah An-Nahdliyyah (JATMAN), Banyumas Branch, in building the spiritual awareness of contemporary youth. Using a qualitative-descriptive approach with an intrinsic case study design, data were collected through method triangulation, comprising in-depth interviews with JATMAN leaders, tarekat murshids, and activists of Mahasiswa Ahlith Thariqah Al-Mu’tabarah An-Nahdliyyah (MATAN), supplemented by participatory observation and institutional document analysis. The findings showed that JATMAN Banyumas successfully integrated modern management principles (planning, organizing, actuating, controlling) with the theosophical value of ihsan through the autonomous youth body MATAN. The da’wah implementation strategy was developed hybridly, combining large-scale physical manaqib assemblies with creative digital content production to reduce the existential anxiety of the millennial and Gen Z generations while eroding the bid’ah stigma imposed by puritan groups. This study’s limitation lies in its geographically specific locus in Banyumas Regency, implying the need for comparative studies with other urban regions. The practical implication offers a blueprint for religious organizations in repackaging Sufi teachings into an adaptive and inclusive spiritual therapy method in the digital era. The originality of this research lies in the theoretical conceptualization of “Transcendental Da’wah Management,” which bridges George R. Terry’s management functions with the esoteric pillar of ihsan and the concept of the spiritual chain of transmission (isnad).